Pemanfaatan Lingkungan Sekolah Sebagai Sumber Belajar Pada Pembelajaran Tematik Kelas III Di SDN 136 Palembang - Taufiqurrahman; Kiki aryaningrum; Robert Budi laksana (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Utilizing the school environment as a learning resource can increase student involvement in the learning process. Contextual learning, involving students in exploring the surrounding environment, can create a deeper and more memorable learning experience. This research aims to find out how the school environment is used as a learning resource in class III thematic learning at SDN 136 Palembang. The method in this research uses descriptive qualitative research methods, where descriptive qualitative is a research approach that focuses on collecting, analyzing and interpreting descriptive data. This approach aims to understand and provide a detailed description of the phenomenon or context being researched. The data collection technique used observation techniques which were carried out before the research, followed by documentation techniques which were collected by the researcher, followed by interview techniques which were carried out together with the principal of SDN 136 Palembang and the homeroom teacher of Class III of SDN 136 Palembang. Thus it can be concluded that the use of the school environment as a learning resource in Class III thematic learning can be used as a learning medium to support the process of teaching and learning activities and can provide good learning outcomes for students and increase student learning motivation.